The relationship between reading comprehension skill assessment methods and academic success for first semester students in a selected Bachelor of Science in Nursing program in Texas. - Cook JDM (Relationship Between Reading Comprehension Skill Assessment Methods & Academic Success for First Semester Students in a Selected Bachelor of Science in Nursing Program in Texas, 2006)
This retrospective descriptive study addressed the relationship between reading comprehension skills as measured by the Nelson-Denny Reading Test and the Nurse Entrance Test and indices of academic success (i.e., grade point average of prerequisite science courses and overall grade point average) prior to admission for students in a Bachelor of Science in Nursing program with student success in the first semester of nursing coursework. Overall, there has been a continual decline in average reading ability of college-aged students. Reading is a basic skill for learning and academic success. To successfully complete an academic program of study in preparation to become professional nurses, students must be able to read and apply material from textbooks and journals. With the well-documented nursing shortage, any attrition from a nursing program contributes to the professional dilemma.Correlational and descriptive methods were used to determine the relationships among the variables for 179 students in this selected Bachelor of Science in Nursing (BSN) program. A comparative approach was used to investigate possible cause and effect relationships between measures of academic success of students and reading comprehension abilities. Data were obtained from official academic records and test results for the Nelson-Denny Reading Test and the Nurse Entrance Test. Statistical procedures used to understand and interpret the interactions among and between the variables and included frequency distributions, descriptive statistics, correlational analysis, and a regression model.Results of the study, limited to the students in this BSN program, indicated that reading comprehension, as measured by the Nelson-Denny Reading Test, was better in identifying student risk for academic failure. There was a positive relationship between the grade point average (GPA) for prerequisite science courses, overall cumulative GPA, and GPA for the first semester nursing courses. Early determination of reading comprehension ability provides needed information to direct intervention activities to improve individual reading comprehension abilities and, thus, promote successful academic performance in the first semester of this nursing program and thereafter.